Qawāʿid al-Fiqh on Government Energy Subsidies: Controlling Inflation Amid Economic Recovery - Firdaus, Nuzulul; Fatwa, Nur (Journal Of Middle East and Islamic Studies, 2025)
The war between Russia and Ukraine significantly affected world life, one of which was the increase in world oil energy prices. Indonesia, in this case, which still imports a lot of energy, is also affected. The government needs to implement policies to face these global challenges, one of which is to provide subsidies for energy so that state budget funds can assist people's purchasing power for energy because if not, this will lead to an increase in the prices of goods and services so that there will be inflation. Still, on the other hand, Indonesia is also carrying out a post-pandemic economic recovery. So that the government is right in carrying out policies, Islamic Economics views this case through sharia principles. This article uses a multidisciplinary approach. The method used is qualitative with a literature study approach. The theory used is the Rules of Qowaid Al-Fiqh, harmonized with Islamic economics. This article highlights that the principles of Islam can also be used in government policies regarding the economy.